Answer:
The final answer is 37/6 = 6.16
Step-by-step explanation:
Given:
[tex]3\frac{2}{6}+(2\frac{1}{6} +\frac{4}{6})[/tex]
We have to work under the parenthesis first.
So
⇒[tex](2\frac{1}{6} +\frac{4}{6} )=\frac{(6*2)+1}{6} +\frac{4}{6}[/tex]
Note : [tex]a\frac{b}{c}=\frac{ac+b}{c}[/tex]
Taking the LCM of the denominators and adding it.
⇒[tex]\frac{13}{6} +\frac{4}{6} =\frac{13+4}{6}=\frac{17}{6}[/tex]
Now we will put this with the earlier values.
⇒[tex]3\frac{2}{6}+\frac{17}{6}[/tex]
⇒[tex]\frac{(3*6)+2}{6}+\frac{17}{6}[/tex]
⇒[tex]\frac{20}{6} +\frac{17}{6} =\frac{20+17}{6}= \frac{37}{6} =6.16[/tex]
After solving the fraction we have 37/6 is our answer in decimal it is 6.16